2015
DOI: 10.1039/c4an02244k
|View full text |Cite
|
Sign up to set email alerts
|

Presence of electrolyte promotes wetting and hydrophobic gating in nanopores with residual surface charges

Abstract: Hydrophobic nanopores provide a model system to study hydrophobic interactions at the nanoscale. Such nanopores could also function as a valve since they halt the transport of water and all dissolved species. It has recently been found that a hydrophobic pore can become wetted i.e. filled with condensed water or an aqueous solution of salt when a sufficiently high electric field is applied across the membrane. The wetting process is reversible thus when the voltage is lowered or switched off, the pore comes ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…The shape of I − V curves and the magnitude of ionic current barely changed with the different KCl concentrations of 0.01, 0.1, 0.2, 0.5, 1 and 2 m in acid condition (Figure S14, Supporting Information), which was different from the concentration‐dependent wetting behavior with the contact angles from 75° to 79°. [ 52 ] The concentration‐independent I − V curves further confirmed there was weak charge effect in hydrophobic nanopore at pH 2 due to the extreme hydrophobicity with the contact angle of 175°. In contrast, the dramatic changes were observed in basic environment with the changes of KCl concentrations (Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
“…The shape of I − V curves and the magnitude of ionic current barely changed with the different KCl concentrations of 0.01, 0.1, 0.2, 0.5, 1 and 2 m in acid condition (Figure S14, Supporting Information), which was different from the concentration‐dependent wetting behavior with the contact angles from 75° to 79°. [ 52 ] The concentration‐independent I − V curves further confirmed there was weak charge effect in hydrophobic nanopore at pH 2 due to the extreme hydrophobicity with the contact angle of 175°. In contrast, the dramatic changes were observed in basic environment with the changes of KCl concentrations (Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
“…The locally enhanced ion concentration could promote wetting, because previous experiments from our group indicated that wetting of hydrophobic nanopores is enhanced in high ionic strength solutions. 23 In order to elucidate which of these phenomena dominates, we prepared a nanopore with one entrance containing a negatively charged polyelectrolyte while the other entrance remained hydrophobic. This system was created by subjecting a nanopore, as schematically shown in Figure 1F, to a solution of polyglutamic acid (PGA).…”
Section: Resultsmentioning
confidence: 99%
“…9 indicate that when water enters the internal pores of BC it becomes constrained and that cations and anions will be tightly held. Innes et al (2015) noted that salt solutions can be tightly held in nanopores depending on the surface charge and the type and concentration of functional groups on the pore surface. XPS results indicated that nitrates and phosphates were detected in BCC after crushing (which allows analysis of the inner surfaces of the particle).…”
Section: Discussionmentioning
confidence: 99%